Research on factors affecting farmers' network information consumption - Meng, H.; Ge, X.; Xie, M. (Journal of Digital Information Management, 2013)
Research on farmers' network information consumption behavior is an important issue, which cannot be avoided in Chinese rural informatization construction. Logit model is used to research the factors affecting farmers' network information consumption, and the conclusions are as follows: 1) there are a number of factors affecting farmers' consumption by using modern network information media; 2) environmental characteristics is the main factor affecting farmers' information consumption via modern network information; 3) younger farmers more often use modern network information media; 4) farmers have a clear purpose by using modern network information media in information consumption, that is, to gain benefits by the use of information. The conclusions of this study will provide a reference for the government to solve the problem in the current informatization construction.
Keywords: Consumption behavior; Farmers; Information consumption; Network